2022
DOI: 10.1182/bloodadvances.2021006645
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of patients with blastic plasmacytoid dendritic cell neoplasm treated with frontline HCVAD

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a clinically aggressive blood cancer, often involving skin, bone marrow, lymph nodes, as well as central nervous system (CNS) involvement in 20-30% of patients. Despite significant progress in CD123- and BCL-2-targeted therapy, most patients are not cured outside of hematopoietic stem cell transplant (HSCT), and CNS relapses are being observed quite frequently. Combination approaches with both targeted and chemotherapy agents plus incorporation of prophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
0
28
0
3
Order By: Relevance
“…Even more recently, an analysis of intensive and CNS active upfront chemotherapy (HCVAD) versus SL-401 did not reveal any CNS relapses in the targeted therapy group. 12 To the best of our knowledge, our case is the first fully published CNS relapse after successful induction treatment with tagraxofusp-erzs. Our case adds to recently published data on CNS involvement in BPDCN.…”
Section: Treatment Of Leptomeningeal Disease In Blastic Plasmacytoid ...mentioning
confidence: 65%
See 1 more Smart Citation
“…Even more recently, an analysis of intensive and CNS active upfront chemotherapy (HCVAD) versus SL-401 did not reveal any CNS relapses in the targeted therapy group. 12 To the best of our knowledge, our case is the first fully published CNS relapse after successful induction treatment with tagraxofusp-erzs. Our case adds to recently published data on CNS involvement in BPDCN.…”
Section: Treatment Of Leptomeningeal Disease In Blastic Plasmacytoid ...mentioning
confidence: 65%
“…Our case adds to recently published data on CNS involvement in BPDCN. 7,8,12 Furthermore, it conveys three important messages: first, LP is an essential initial diagnostic procedure in BPDCN, also in the context of therapy with tagraxofusp-erzs. Due to their distinct morphology and aberrant immunophenotype BPDCN cells can be easily detected (Figure 1B and C).…”
Section: Treatment Of Leptomeningeal Disease In Blastic Plasmacytoid ...mentioning
confidence: 99%
“…The use of HyperCVAD as a first-line regimen is supported by recent evidence also published by Pemmaraju et al, in 2021, with a retrospective series of 100 patients from 1999 to 2020, of which 35 received any combination of this regimen, 37 received tagraxofusp, and 28 received other treatments. Despite the methodological limitations, it calls to attention that the patients who received the HyperCVAD regimen achieved a higher complete remission (80% vs. 59% vs. 43%, p=0.01), although with no differences in overall survival (OS) and with similar post-HSCT outcomes [15]. In this way, it is concluded that HyperCVAD-type chemotherapy schemes can continue to be considered first-line treatment, and prospective studies are required to evaluate the comparative efficacy of other treatments such as tagraxofusp in monotherapy or in combination with traditional chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of cytotoxic programs used by experts in older/unfit BPDCN include mini-cyclophosphamide, vincristine, and prednisone (CVD) regimen (HCVAD minus the anthracycline; reduction of doses of all agents with particular focus on creatinine and myelosuppression/infection/sepsis risk); cyclophosphamide, doxorubicin, vincristine and prednisolone (CHOP) lymphoma-based regimen; dose reduced AML-based regimens. 22 , 26 , 29 , 40 , 41 …”
Section: Recommendations and Proposalsmentioning
confidence: 99%
“… 39 Furthermore, several reports across the world have demonstrated the safety and efficacy of combinations of ventoclax either with chemotherapy (HCVAD plus VEN) or combinations with CD123-based agents, providing a novel approach to older/unfit patients or even for younger patients or those with resistant to disease to frontline approaches. 34 , 40 …”
Section: Recommendations and Proposalsmentioning
confidence: 99%